Synthesis and antimicrobial evaluation of substituted fluoroquinolones under conventional and microwave irradiation conditions - Prasad, Mutyala Veera Venkata Vara; Veranna, Vadde; Rao, Radha Hunasenahalli Raghavendra; Darsi, Sai Subramanyam Praveen Kumar (European Journal of Chemistry, 2017)
A series of new fluoroquinolones analogs (3a-i) were prepared under conventional and microwave irradiation technique. Ethyl 1-cyclopropyl-6,7-difluoro-8-methoxy-4-oxo-1,4-dihydroquinoline-3-carboxylate (1) on reaction with boric acid and acetic anhydride in the presence of catalytic amount of zinc chloride under reflux, resulted in an unstable borate complex. Which was instantaneously treated with morpholine, piperidine, thiomorpholine, 2,6-dimethylmorpholine, 4,5,6,7-tetrahydrothieno[3,2-c]pyridine hydrochloride, 5,6,7,7a-tetrahydrothieno[3,2-c]pyridin-2(4H)-one hydrochloride, 2,3-dichlorophenylpiperazine hydrochloride, 3-(piperidin-4-yl)benzo[d]isoxazole hydrochloride and 5,6,7,8-tetrahydro-[1,2,4] triazolo[4,3-a]pyrazine, in the presence of triethylamine to yield compounds 3a-i. The same compounds on the other hand synthesized using a microwave irradiation technique in the presence of triethylamine and adsorbed neutral alumina. The structures of the synthesized compounds were established on the basis of spectral and analytical data. The antimicrobial activity of newly synthesized compounds were evaluated against different microorganisms and found the compounds exhibited significant activity.